The Relationship Between Tourism Development with Primary Forest in Indonesia - Simatupang, Aldo Gadra Paulus; Soetjipto, Widyono (Jurnal Wilayah dan Lingkungan, 2025)
To further develop Indonesian tourism, the Indonesian government designed a program to develop 10 new Indonesian "Bali" destinations.  The majority of these new 'Bali' destinations are located outside Java Island that contain primary forests with high endemic species. Since 2004, Indonesia’s government have released several policies to further develop tourism destination outside of Bali such as Rencana Induk Pembangunan Kepariwisataan Nasional (RIPPARNAS) dan Destination Management Organization (DMO). The relationship between tourism development and forest cover is a subject of active discussion, and there is little empirical research on the topic. This study aims to examine the correlation of tourism development (hotel beds) with primary forest cover. The data used in the study are Global Forest Watch’s forest cover image data, Global Administration Data System’s land cover data, and Indonesia Central Agency of Statistics socio-economic publication data from 32 Indonesian provinces in 2011-2016. Through the use of a clustered fixed effects regression model, this study found that tourism has no significant relationship with primary forest area in Indonesia.